Políticas públicas de formação continuada dos professores do ensino médio: um estudo da rede estadual de Pernambuco - Marcelino, Angélica de Cássia Gomes (2015)
This study aimed to investigate the continuing education policy for high school teachers of the state of Pernambuco (Brazil) between 2011-2014, considering the education management model implemented since 2007 by the Pernambuco’s Secretariat of Education in the program entitled: “Modernizing Management”, which set up since then as a program focused on improving the educational indicators of this state, working to manage for results. The main objective of this policy was to consolidate the culture of democracy and popular participation in educational units, based on diagnosis, planning and management (Pernambuco, 2009). In this educational management perspective, we investigated how was developed the continuing education of high school teachers and how teachers conceive and materialize these formations in Pernambuco. We seek to understand the possible contributions to the pedagogical practice of teachers and possible limitations of the continuing training policy for basic education teachers in Pernambuco. To understand how did this continuing policy in Pernambuco we investigated subjects belonging to two public schools located in the city of Goiás, at this state, that offer high school. Use the line of investigation from the perspective of qualitative approach in which it was performed a literature study based on the theoretical contribution as Brzezinski (2001; 2008; 2014), Gatti (2008; 2011), Kuenzer (2011), Freitas (2015), Gold (2012; 2014), Freire (1981; 1985; 1991; 1992; 1993; 2011; 2013), authors who discuss the continuing education of teachers. We also did an analysis of the legal documents that enable, within the Pernambuco’s Secretariat of Education and at the national level, the process of continued education throughout education network. We also use semi-structured interview as a tool for data collection that was applied between school managers, support educators, the responsibles for training and studies in the school context, as well as among the teachers who work in high school and have participated in continuing education network between 2011-2014. Also took advantage Freire’s conceptual plots that have been studied and published by Unesco’s Paulo Freire Cathedra. We raise the Freire categories that have been identified in the reports of professionals and how these speeches denouncing the resistance and indignation in the face of current practices of continuing teacher education. This research exposes the desire to changes in training practices of high school teachers of the Pernambuco state system, from the look of the individuals to whom these practices are being designed in order to contribute to the discussion of a continuing education emancipating teachers and based on an integral formation of the person.